Diversity of Parasites in Two Sympatric Species of Brazilian Tetras (Characiformes: Acestrorhamphidae) in the Caatinga Domain, Northeastern Brazil - Bruno Anderson Fernandes da Silva; Julia Martini Falkenberg; Fábio Hideki Yamada (Parasitologia)
This study investigates the parasitic biodiversity of the fish species Astyanax bimaculatus and Psalidodon fasciatus in a stream located in the Chapada do Araripe Environmental Protection Area (APA), state of Ceará, Brazil, contributing to the understanding of parasitic fauna diversity of freshwater fish in neotropics. In total, 292 fish specimens were collected and analyzed, identifying 13 parasite taxa in A. bimaculatus and 11 in P. fasciatus. Several parasite groups were identified, including myxozoans, monogeneans, digeneans, and nematodes. The host A. bimaculatus exhibited a higher number of parasite taxa and abundance compared to P. fasciatus. The lower sample size for P. fasciatus reflects its naturally lower abundance in the wild, but the analyses accounted for sampling bias, ensuring comparisons of the parasite communities of these two fish species. The parasite communities of both species showed high similarity, indicating potential host-switching or co-evolutionary patterns. Positive correlations were observed between parasite diversity, species richness, abundance, and host weight/length. The study expands the knowledge of parasite–host associations and the geographical distribution of parasite species in Northeastern Brazil, a region where such data remain underreported.